PENGARUH DOSIS FUNGISIDA DAN PERIODE PENYIMPANAN TERHADAP VIABILITAS BENIH KAKAO (Theobroma cacao L.) - Tati Budiarti; , Yulmiarti (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1997)
The experiment of seed treatment and storage longevity on cacao seed valiability was. conducted at Seed Science and Technology Laboratory, Departement of Agronomy, Faculty of Agriculture, Bogor Agriculture University since March to July 1995. The objectives of this experiment were to find out the optimum dosage of fungicide treatment and storability on cacao seed. Split plot design was used in this experiment; main plot were storage periods i.e. I, 3, 5, 7, and 9 weeks and .sub plots were dosages of fungicide (active ingredient carbendazim + mankozeb) 0, 2, 4, 6, g/kg of ,seed with 3 replication. Each unit consisted of 40 seeds. Result (the experiment indicated that control seed (without fungicide) were infected by fungi 90.67 % on the first week and its germination capacity was only 57.33 %. Fungi infection increased rapidly after 1 week and its caused the viability lost. Application of 2, 4, 6 g fungicide/kg of seeds inhibited fungi growth and that treatments maintained seed viabilility until 9 weeks of storage periods. There are no significant difference among fungicide dosage, except on index vigor; application of 4 and 6 g (of fungicide result lower index vigor. Better fungicide dosage was4 .21g/kg of seeds based on quadratic regression Y = 20.80 + 43.10 X - 5.12 X2 (Y = germination capacity, X = dosage fungicide). Dominant fungi infected on seed storage were identified as Fusarium sp and Aspergillus sp. The storability of cacao seed with fungicide treatments on 9 weeks of storage period were still relatively high, the germination capacity more than 80% and the seeding vigor were not different among of all storage periods